Study on Translating Subjectless Sentences in the China’s Energy Transition White Paper - Li, Jiani (International Journal of Social Sciences and Public Administration, 2025)
Subjectless sentences, a notable feature of Chinese, are prevalent in political texts but pose challenges in English translation due to a reliance on explicit subjects, potentially impeding cross-cultural communication. This study aims to explore effective translation strategies for such sentences in Chinese political texts, focusing on how to convey their meaning accurately while retaining the original stylistic features. Taking China’s Energy Transition White Paper (2024) (issued by the State Council Information Office) as the research object, it analyzes typical subjectless sentences and examines four key strategies: passivization, syntactic rephrasing, supplementation of logical subjects, and insertion of formal subjects. Findings show that context-adaptive strategy selection is critical for accurate rendering, enhancing the international readability of political texts. This study offers practical guidance for translators and enriches research on linguistic differences in political discourse translation.